ANALISIS PENGARUH RASIO KEUANGAN, PERTUMBUHAN PENJUALAN DAN DIVIDEN TERHADAP PERUBAHAN HARGA SAHAM PERUSAHAAN CONSUMER GOODS - Yusuf Yoga Adi Surya (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2016)
This study aims to determine the effect of financial ratio i.e the ratio of liquidity and profitability to the stock price; the influence of sales growth on stock prices; and the effect of dividends on stock prices at the consumer goods company field of telecommunications services. This study used a sample of three telecommunications companies listed in Indonesia Stock Exchange, namely: PT Indosat, PT Telkom and PT XL Axiata with financial reporting data from 2011 to 2015. The method of analysis using multiple linear regression analysis as an analytical tool for analyzing the effect of the finance ratio, sales growth and dividends. Getting the results that the current ratio of significant positive effect on the stock price changes with stats t = 3.888, p = 0.002 <0.05. Return on equity is not significant positive effect on the stock price changes with stats t = 0.807, p = 0.437> 0.05. The sales growth was not significant positive effect on the stock price changes with stats t = 1.068, p = 0.311> 0.05. Dividend payout ratio is not significant positive effect on the stock price changes with stats t = -0.462, p = 0.654> 0.05.